Avaliação do efeito do disseleneto de difenila na nocicepção induzida pela administração neonatal de glutamato monossódico em ratos - Rosa, Suzan Gonçalves (2014)
Monosodium glutamate (MSG) has been the target of research due to its toxicological effects. Neonatal administration of MSG in animals can affect the morphological and electrophysiological organization of the brain, leading to behavioral disorders in adulthood, including increased pain sensitivity. The present study aimed to investigate the mechanism of action by which MSG induces nociception and the effect of diphenyl diselenide (PhSe)2, an organoselenium compound with pharmacological properties already documented, on nociception induced by MSG. Newborn Wistar rats were treated with ten subcutaneous injections of MSG at a dose of 4.0 g/kg or saline, once a day. At the 60th day of life, rats received daily (PhSe)2 (1 mg/kg) or vehicle (canola oil) by intragastric route for 7 days. The behavioral tests (locomotor activity, hot plate, tail-immersion and mechanical allodynia) were carried out. In addition, hippocampal ex vivo assays were performed to determine Na+, K+-ATPase and Ca2+-ATPase activities, cytokines levels and [3H] glutamate uptake. The results demonstrated that MSG increased nociception in the hot plate test, but not in the tail immersion test, and in the mechanical allodynia stimulated by Von-Frey Hair. (PhSe)2 decreased all nociceptive behaviors induced by MSG. MSG increased hippocampal Na+,K+-ATPase and Ca2+-ATPase activities and pro-inflammatory cytokines levels as well as decreased the anti-inflammatory cytokine (IL-10) and the [3H]glutamate uptake in hippocampi of rats. (PhSe)2 treatment protected against these alterations. These results demonstrated the mechanisms of action involved in nociception induced by MSG and the antinociceptive action of (PhSe)2 after neonatal injections of MSG in rats through the decrease hippocampal excitotoxicity and neuroinflammation associated to the administration of MSG in rats.